Understanding the Care Experiences and Support Needs of UK Adults Treated in Hospital for Meningitis - Harriet Hay; Amy Tallett; Bec Aeddi; Beverley Corbett; Claire Donovan; Jane Blewitt; Juan Abad Madroñero (Patient Experience Journal)
Background: Meningitis often results in ongoing and multifaceted after-effects, which can impact many aspects of people's lives, yet relatively little support and follow-up is offered. This study explored post-treatment care experiences of UK adults aged 16 and over following a recent stay in hospital for meningitis. Methods: A survey was designed to ask about hospital discharge, recovery, information provision and aftercare support. The research involved 5 semi-structured, in-depth interviews and a 15-participant online asynchronous focus group. The themes arising from this qualitative stage informed the development of a quantitative 32-item questionnaire which was hosted and promoted online between September 2022 and February 2023. Results: Two hundred and twenty-eight survey responses were received. Respondents reported ongoing impact to many aspects of their lives. Many did not feel they received enough information or signposting to appropriate and tailored support services, despite reporting they would have liked this. A lack of care continuity was reported at discharge through to primary, secondary, and tertiary care. Conclusions: Although meningitis affects a small proportion of adults, it can have a substantial impact on the lives of those who have suffered from it. Regardless of the cause of meningitis, the findings highlighted gaps in information provision, awareness, follow-up care, and support for adults. We recognise the limitations of recruiting for and hosting the survey solely online. Findings have been submitted to the National Institute for Care and Excellence (NICE) for consideration in the current development of new guidelines for bacterial meningitis and meningococcal disease.